Decision-making based on the model of functioning of socio-ecological-economic system - Zhukov, Roman; Kozlova, Nadezhda; Plinskaya, Maria; Myasnikova, Elena; Melay, Elena (E3S web of conferences, 2023)
The development of regional socio-economic and ecological systems requires informed decisions. In this, decision-making authorities can be helped by models of such systems, which include three interrelated subsystems: social, environmental and economic, which may include subsystems of a lower level. The object of the study is hierarchical socio-ecological-economic systems (SEES) with homogeneous performance characteristics at all levels of management. The subject of the study is the characteristics of the processes of influence of factors on the results of the functioning of a hierarchical SEES in order to develop control actions that provide a given level of target indicators. The purpose of the study is to model the functioning of socio-ecological and economic systems based on a multi-level optimization approach under conditions of uncertainty, with the help of which it is possible to find changes in factors that allow improving the goal indicators of the SEES functioning. Based on the constructed models of the state and functioning of complex systems for the regions of the Central Federal District and the Tula Region using statistical data for 2007-2020, a multilevel optimization approach to the management of socio-economic systems was applied, proposals aimed at ensuring the sustainable development of the Tula region in the ecological subsystem were substantiated.